2011
DOI: 10.3892/mmr.2011.437
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle tissue from the Goto-Kakizaki rat model of type-2 diabetes exhibits increased levels of the small heat shock protein Hsp27

Abstract: Abstract. in order to increase our understanding of diabetes-related muscle weakness, we carried out a mass spectrometry-based proteomic analysis of skeletal muscle preparations from the Goto-Kakizaki rat model of type-2 diabetes. Fluorescence difference in-gel electrophoresis was performed to determine potential differences in the global protein expression profile of muscle extracts. Besides changes in contractile proteins and metabolic enzymes, the abundance of the small stress proteins αB-crystallin and Hsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…HSPB1 participates in the regulation of apoptosis, protects the cell against oxidative stress, and is involved in the regulation of the cytoskeleton [49]. In turn HSPB1 has been related to better fatigue resistance [50] and has been shown to be up-regulated in animal models of diabetes-related muscle weakness [51]. Moreover, it has been reported that the chaperone effect of CRYAB on the cytoskeleton in relation to tubulin/microtubule, is a key mechanism for muscle adaptation, muscle differentiation and protection from atrophy [52].…”
Section: Discussionmentioning
confidence: 99%
“…HSPB1 participates in the regulation of apoptosis, protects the cell against oxidative stress, and is involved in the regulation of the cytoskeleton [49]. In turn HSPB1 has been related to better fatigue resistance [50] and has been shown to be up-regulated in animal models of diabetes-related muscle weakness [51]. Moreover, it has been reported that the chaperone effect of CRYAB on the cytoskeleton in relation to tubulin/microtubule, is a key mechanism for muscle adaptation, muscle differentiation and protection from atrophy [52].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, several research groups have performed skeletal muscle proteome analysis from diabetic patients and rodent models of diabetes [68,69,70,71]. These pioneering studies have already begun to advance our understanding of skeletal muscle insulin resistance.…”
Section: Proteome Profiling Of Diabetic Skeletal Musclementioning
confidence: 99%
“…Another study that involved proteome analysis of lean, obese and Type 2 diabetic skeletal muscles revealed that the insulin-resistance muscle bears reduced expression of mitochondrial and structural proteins [72]. These abnormalities were also observed in skeletal muscle from rodent model of Type 2 diabetes [71]. Using two-dimensional electrophoresis combined with mass spectrometry, Choi et al demonstrated gender specific differences in rodent model for Type 2 diabetes [73].…”
Section: Proteome Profiling Of Diabetic Skeletal Musclementioning
confidence: 99%
“…The proteomic profiling of crude muscle extracts and subcelluar fractions from the Goto-Kakizaki rat has employed different protein staining methods for the visualization of protein spots in two-dimensional gels, that is, colloidal Coomassie Blue [82], fluorescent RuBPs [82, 83], and fluorescent CyDyes for difference in-gel electrophoretic analysis [83, 84]. The different labeling techniques clearly showed variations in their dynamic visualization range, so proteomic findings from the 3 dyes used for densitometric scanning could be combined for a more complete coverage of changes within the diabetic muscle proteome.…”
Section: Proteomic Profiling Of Diabetes Mellitusmentioning
confidence: 99%
“…The different labeling techniques clearly showed variations in their dynamic visualization range, so proteomic findings from the 3 dyes used for densitometric scanning could be combined for a more complete coverage of changes within the diabetic muscle proteome. Colloidal Coomassie staining, routinely used for reliable protein detection following gel electrophoresis [114, 115], and fluorescence difference in-gel electrophoresis, which represents one of the most powerful biochemical tools for the comparative analysis of protein complements [116118], resulted in the detection of 929 [82] and 1734 [83] protein spots, respectively. The silver staining technique and protein labeling with the fluorescent RuBPs dye (ruthenium bathophenanthroline disulfonate) [119] were employed as independent visualization methods for the verification of key findings in altered protein expression patterns [82, 83].…”
Section: Proteomic Profiling Of Diabetes Mellitusmentioning
confidence: 99%